Morality with an Accent - Romney, Douglas (Stance: an international undergraduate philosophy journal, 2019)
In this paper, the difficulties inherent in the debate between moral nativists and antinativists, who differ in their beliefs on the nature of systems of morality, are shown to exemplify the need for philosophers to support their views with empirical data. Furthermore, it proposes that an empirical study of first-generation immigrant populations has the potential to resolve the debate over moral nativism, as it would allow researchers to observe the moral “critical period.” Based on the recent philosophical advances made through experimental evidence, this paper goes on to argue that empirical data is a valuable source of information from which philosophers ought to draw.